Validity and reliability of visual analog scale foot and ankle: The Turkish version - Gür, Gözde; Turgut, Elif; Dilek, Burcu; Baltacı, Gül; Bek, Nilgün; Yakut, Yavuz (Elsevier Science Inc, 2017)
The present study tested the reliability and validity of the Turkish version of the visual analog scale foot and ankle (VAS-FA) among healthy subjects and patients with foot problems. A total of 128 participants, 65 healthy subjects and 63 patients with foot problems, were evaluated. The VAS-FA was translated into Turkish and administered to the 128 subjects on 2 separate occasions with a 5-day interval. The test-retest reliability and internal consistency were assessed with the intraclass correlation coefficient and Cronbach's alpha. The validity was assessed using the correlations with Turkish versions of the Foot Function Index, the Foot and Ankle Outcome Score, and the Short-Form 36-item Health Survey. A statistically significant difference was found between the healthy group and the patient group in the overall score and subscale scores of the VAS-FA (p < .001). The internal consistency of the VAS-FA was very good, and the test-retest reliability was excellent. Adequate to good correlations were found between the overall VAS-FA score and the Foot Function Index, Foot and Ankle Outcome Score, and Short-Form 36-item Health Survey scores in the healthy and patient groups both. The Turkish version of the VAS-FA is sensitive enough to distinguish foot and ankle-specific pathologic conditions from asymptomatic conditions. The Turkish version of the VAS-FA is a reliable and valid method and can be used for foot-related problems.
WOS: 000414222400016
PubMed ID: 28864388
Keywords: Foot Problems; Internal Consistency; Outcomes Assessment; Questionnaire Test-Retest Reliability; Turkish; Validation; VAS-FA